Pengaruh Kualitas Produk, Harga dan Lokasi Terhadap Keputusan Pembelian Kerajinan Tas pada Awi Handmade Kediri - Yudha Dwi Pradita; Zaenul Muttaqien; Lina Saptaria (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to explain the influence of product quality, price and location on purchasing decisions at Awi Handmade Kediri. The data analysis technique used by researchers in this study uses statistical tests through validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t tests, F tests with SPSS version 16.0. The methods used in this study are questionnaires, interviews and observations. The sampling technique in this study used the Accidental Sampling technique with a sample size of 86. Based on the results of the study obtained by researchers from the multiple linear regression equation Y = 2.344 + 0.369X1 + 0.411X2 + 0.2.69X3. The results of the analysis conducted, the results of the study indicate that the product quality variable has a significant effect on purchasing decisions, the price variable has a significant effect on purchasing decisions with evidence of Sig t 0.000> 0.05, the location variable has a significant effect on purchasing decisions with evidence of Sig t 0.000 <0.05, and the results of product quality, price and location simultaneously have a significant effect on purchasing decisions with evidence of Sig F 0.000 <0.05. The results of the analysis of the R2 value = 0.907 or 90.7%.